Gündelik yaşamda kişilerarası iletişim : bir yapılandırılmış kuram oluşturma çalışması - Yılmaz, Orhun Doğuş (My University, 2021)
Bu tez, gündelik yaşam çalışmaları ve kişilerarası iletişim çalışmalarının ortaklığının anlaşılması, kişilerarası iletişim pratikleri ve gündelik yaşam pratiklerinin bütüncüllüğünün daha iyi kavranmasına vurgu yapma amacı gütmektedir. Bu bağlamda, çalışma, ilkin kişilerarası iletişimin ve gündelik yaşam çalışmalarının mevcut disiplinel yapısını anlamak için tarihsel geçmişini ve gelişimsel süreçlerini de kapsayacak eleştirel bir literatür taraması yapacak ardından gündelik kişilerarası iletişimin yapısal unsurlarını anlamak üzere yapılandırılmış bir kuram oluşturma çalışması yöntemi kullanılarak bir gündelik kişilerarası iletişim modeli önerecektir.

Everyday life, is the homeland of our behaviours and thinking processes. Clarification of the daily, is the datum point of understanding and identifying all the activities we do during the day. This comprehensiveness of the Everyday life, makes it extremely important. However it also turns it to an area which is very hard to study on. Everyday life is the amount of the adaptation process of our physical and mental activities. The Everyday life is a test for our adaptation process, our social skills. During this life, our activities are being tested and usually being negatified. Since all these daily elements related to each other, they have their own type of interaction. As a result of this interaction, the Everyday life gains it's meaning only by doing collective readings. By it's very nature, interpersonal communication is a daily activity. It functions as a social mechanism which organizes relational construcion by using interactional progresses. This mechanism still feels the post-positivist and behaviroist affect of social psychology. As a result of this affect, it does not contain the daily activities. It has a history which is limited by macro-microscale studies. A Everyday life which is not studied without the required sterilization would come into conflict with behaviorist sutructure of communication studies. By their own very nature, these two elements cannot be studied by using empirical methods.The point of this thesis is to underline the common points of the studies made on the subject of Everyday life and interpersonal communication. This thesis also aims to create a field to do a better reading on practices of interpersonal communication and Everyday life.In consequence of a literature reviews and qualitative studies which is completed in this context, unique daily inter-personal communication is being recommended. Firstly, the study will touch on the history of interpersonal communication to understand the disciplinal construction of it. Then, by reviewing the multi-disciplinal constructure of interpersonal communication, structural elements of daily interpersonal communication will be explored. Finally, a grounded theory will be creating in the light of all these steps mentioned before and a model of a daily interpersonal communication will be suggested.
Keywords: Constructing Grounded Theory; disiplinlerarasılık Everyday life; everyday interpersonal communication; gündelik kişilerarası iletişim; Gündelik yaşam; Interpersonal communication; Interpersonal relations; interdisciplinarity; Kişilerarası iletişim; Kişilerarası ilişkiler; yapılandırılmış kuram oluşturma